A co-evolutionary approach to understanding construction industry innovation in renovation practices for low-carbon outcomes. (February 2018) - Killip, Gavin; Owen, Alice; Morgan, Elizabeth; Topouzi, Marina
Energy consumption in buildings is a large contributor to global carbon dioxide emissions. Renovations of existing buildings can reduce their impact by integrating technologies which increase efficiency or generate renewable energy on-site. Doing this well and at scale is a collective action problem, which transcends the agency of individual entrepreneurs. This article reports a cross-case comparison of four previous studies focused on low-energy renovation of housing, using a co-evolutionary framework in which five systems are mutually interdependent: ecosystems, technologies, user practices, business strategies and institutions. Innovations across the five systems are described in terms of variations, selection pressures and transmission. The analysis draws out common themes from the four previous studies and to reflect on how well the co-evolutionary framework accounts for innovation in the particular field of housing renovation for low-energy outcomes. Business strategies emerge as an important (and often neglected) source of innovation. The framework generally accounts for innovation in this area quite well, although two important issues are a less easy fit: The use of energy (and other finite resources) is rather indirectly accounted for by the term 'ecosystems' and the complexity of interactions between multiple users, businesses and technologies is partly elided.